Deep medullary veins score is associated with atrophy in patients with cerebral small vessel disease - Mao, Fan; Xu, Zhihua; Shao, Meihua; Xiang, Xuelian; Zhou, Xiaoli (Frontiers in Neurology, 2024)
Objective To explore the relationship between the deep medullary vein (DMV) score and atrophy in patients with cerebral small vessel disease (CSVD). Methods Imaging and clinical data from 125 patients with CSVD from January to December 2022 were reviewed. Normalized gray matter volume (GM_N) was calculated by dividing the gray matter volume by the whole brain volume. DMV scoring is conducted using susceptibility-weighted magnetic resonance imaging, wherein the DMV area is partitioned into six distinct regions: bilateral frontal, parietal, and occipital regions. Each region undergoes assessment based on the clarity and consistency of DMV visibility. Subsequently, the scores from these six regions are summed, resulting in a score ranging from 0 to 18 points. Results DMV score was associated with GM_N (r = −0.376, p < 0.001). Comparisons among patients according to GM_N tertiles, differences in gender, age, current smoking, DMV score, and total CSVD magnetic resonance imaging score were demonstrated (p < 0.05). Adjusting for age, gender, vascular risk factors, and total CSVD MR score, the DMV score was independently associated with GM_N [β (95% CI): −0.347 (−0.525, −0.168), p < 0.001]. Conclusion DMV scores are independently associated with GM_N, and DMV dysfunction may play a role in brain atrophy.